Changing attitudes, beliefs and feelings towards food in bulimic patients - Marle Santos Alvarenga; Fernanda Baeza Scagliusi; Sonia Tucunduva Philippi (Archivos Latinoamericanos de Nutrición)
Eating attitudes are defined as beliefs, thoughts, feelings and behaviors towards food. Bulimia nervosa (BN) is an eating disorder, in which the eating attitudes are seriously disturbed. Studies that evaluated nutritional aspects of BN focus mainly on food intake, dietary restriction and binge eating, while the follow-up studies evaluate mainly clinical symptoms. The objective of this study was to evaluate eating attitudes of patients with BN, during and after cognitive-behavioral intervention. Thirty nine (39) BN female patients received cognitive behavioral treatment with a multidisciplinary team and had eating attitudes assessed by a questionnaire developed for this research. Frequencies of the attitudes assessed were compared at baseline, after 12 weeks and 24 weeks of treatment. After treatment, patients had less distorted beliefs about food, less guilty after eating “forbidden” foods and they felt more tranquil while eating outside home. Other negative behaviors, as dietary restriction, the desire of not eat, being angry when feeling hungry and using the food to relive stress, persisted. Eating attitudes of patients with BN are hard to be changed in a short-term. More attention to this disease’s component and new approaches to treatment are needed in order to have a better recovery.